Tret'ia Meshchanskaia - Room, Abram (Soviet Union, 1927)
A married couple has a small apartment in Moscow. When an old friend of the husband's arrives in the city, he is unable to find lodgings. Kolia, the husband, invites his friend to move in with them. While Kolia is away on business, sensual Liuda and attractive Volodia fall in love and have an affair. After his initial outrage, the husband calms down. Kolia winds up on the sofa, and the three settle into a menage-a-trois until the wife finds herself pregnant. The two men are trying to decide what to do, but Liuda is strong enough to make her own decisions. Considered a landmark film because of its humor, naturalism, and sympathetic portrayal of the woman.
Keywords: Fiction films